Transmission of Human and Macaque Plasmodium spp. to Ex-Captive Orangutans in Kalimantan, Indonesia - Michael J.C. Reid; Raul Ursic; Dawn Cooper; Hamed Nazzari; Melinda Griffiths; Birute M. Galdikas; Rosa M. Garriga; Mark Skinner; Carl Lowenberger (Emerging Infectious Diseases, 2006)
Data are lacking on the specific diseases to which great apes are susceptible and the transmission dynamics and overall impact of these diseases. We examined the prevalence of Plasmodium spp. infections in semicaptive orangutans housed at the Orangutan Care Center and Quarantine, Central Kalimantan, Indonesia, by using a combination of microscopic and DNA molecular techniques to identify the Plasmodium spp. in each animal. Previous studies indicated 2 orangutan-specific Plasmodium spp., but our data show 4 Plasmodium spp. These findings provide evidence for P. vivax transmission between humans and orangutans and for P. cynomolgi transmission between macaques and orangutans. These data have potential implications for the conservation of orangutans and also for the bidirectional transmission of parasites between orangutans and humans visiting or living in the region.